2017
DOI: 10.1186/s12969-017-0151-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic damage in hands and wrists of patients with juvenile idiopathic arthritis after 29 years of disease duration

Abstract: BackgroundThere are few studies on radiographic outcome after long-term disease duration in juvenile idiopathic arthritis (JIA). We wanted to evaluate 29-year radiographic outcome in hands/wrists and predictors of damage in patients with long-term active JIA.MethodsPatients diagnosed from 1980 to 1985, who had active disease at 15-, 23- or 29-year follow-up and arthritis in the wrists during the disease course, were reexamined with radiographs of hands/wrists. We used the adapted version of the Sharp van der H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
6
1
2
Order By: Relevance
“…In fact, it has been demonstrated that ACPA detected in pJIA RF+ patients express the inherently autoreactive 9G4 idiotope, which supports an activation of autoreactive 9G4+ B cells in JIA ( 148 ), similarly to what has been described in RA patients ( 149 ). Importantly, ACPA detection in JIA patients is associated to more severe and erosive disease progression, which might implicate an earlier and more intensive treatment ( 8 , 112 114 , 146 , 150 , 151 ). During inflammation, ACPA might be produced in a process called citrullination, a post-translational modification catalyzed by peptidylarginine deiminases (PAD) enzymes in which arginine amino acid residues are enzymatically converted into citrulline residues in a wide range of proteins ( 152 , 153 ).…”
Section: B Cell Roles In Juvenile Idiopathic Arthritis Pathophysiologymentioning
confidence: 99%
“…In fact, it has been demonstrated that ACPA detected in pJIA RF+ patients express the inherently autoreactive 9G4 idiotope, which supports an activation of autoreactive 9G4+ B cells in JIA ( 148 ), similarly to what has been described in RA patients ( 149 ). Importantly, ACPA detection in JIA patients is associated to more severe and erosive disease progression, which might implicate an earlier and more intensive treatment ( 8 , 112 114 , 146 , 150 , 151 ). During inflammation, ACPA might be produced in a process called citrullination, a post-translational modification catalyzed by peptidylarginine deiminases (PAD) enzymes in which arginine amino acid residues are enzymatically converted into citrulline residues in a wide range of proteins ( 152 , 153 ).…”
Section: B Cell Roles In Juvenile Idiopathic Arthritis Pathophysiologymentioning
confidence: 99%
“…Current methods to monitor destructive events are clinical evaluation in combination with radiographic imaging that identifies changes in the joint structure and joint space caused by loss of articular cartilage and bone. However, these methods are insensitive and mainly detect late stages of destruction (7,8). Joint destruction often progresses from the cartilage surface to the subchondral bone and leads to structural degradation and release of molecular fragments of the joint into biologic fluids, which could be used as biomarkers (9).…”
Section: Introductionmentioning
confidence: 99%
“…Это первый препарат на российском рынке, который воздействует на механизм заболевания в его ключевом звене и при-останавливает его дальнейшее развитие. Результаты нескольких международных рандомизированных пла-цебоконтролируемых исследований показали высокую эффективность препарата для лечения как системных проявлений болезни, так и уменьшения степени деструк-ции суставов, а также хороший профиль безопасности препарата [21][22][23].…”
Section: обсуждение основного результата исследованияunclassified
“…Обычное рентгенологическое исследование остается «золотым стандартом» для выявления структурного пора-жения суставов и нарушения костей у пациентов с ЮИА [23]. Для оценки рентгенологического прогрессирова-ния суставной деструкции часто используют модифи-цированный метод Шарпа (Sharp/van der Heijde), реко-мендованный Европейской антиревматической лигой (EULAR).…”
Section: обсуждение основного результата исследованияunclassified